LEGAL CERTAINTY AND EMPLOYER LIABILITY FOR OCCUPATIONAL HEALTH AND SAFETY (OHS) THROUGH PPE IN THE RICE MILLING INDUSTRY - Rafa Rizqullah; Deni Yusup Permana (Fakultas Hukum Universitas Swadaya Gunung Jati, 2026)
Occupational Safety and Health (OSH) protection constitutes a fundamental right of workers and a legal obligation of employers as guaranteed under Indonesian labor law. One of the primary forms of such protection is the provision of Personal Protective Equipment (PPE), which functions to minimize the risk of occupational accidents and work-related diseases. This study aims to analyze the normative regulation of employers' obligations to provide PPE for workers in the rice milling industry and to examine the legal liability of employers who fail to fulfill such obligations. This research employs a normative legal research method, drawing on statutory, conceptual, and descriptive-analytical approaches. The legal materials consist of primary legal sources, such as legislation, and secondary legal sources, including books, scientific journals, and expert opinions. The findings indicate that the obligation to provide PPE has been regulated hierarchically and comprehensively through the 1945 Constitution of the Republic of Indonesia, Law Number 1 of 1970 concerning Occupational Safety, Law Number 13 of 2003 concerning Manpower, Government Regulation Number 50 of 2012 concerning Occupational Safety and Health Management Systems, and Minister of Manpower Regulation Number PER.08/MEN/VII/2010 concerning PPE. From the perspective of legal certainty theory, these regulations provide clear guidance regarding workers' rights and employers' obligations. Nevertheless, normative weaknesses remain in the sanctioning mechanism, particularly because sanctions are no longer proportional to contemporary labor conditions. Employers who fail to provide PPE may be held administratively, civilly, and criminally liable under applicable laws and regulations.